2023
DOI: 10.1021/acsmaterialslett.2c00997
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlooping Carbon Nanotube-Graphene Oxide Nanoarchitectonics as Membranes for Ultrafast Organic Solvent Nanofiltration

Abstract: Membrane technology is a key enabler for a circular pharmaceutical industry, but chemically resistant polymeric membranes for organic solvent nanofiltration (OSN) often suffer from lower-than-required performances. Recently, graphene-based laminated membranes using small-flake graphene oxide (SFGO) nanosheets open up new avenues for high-performance OSN, but their permeance toward high viscosity solvents is below expectation. To address this issue, we design hyperlooping channels using multiwalled carbon nanot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 70 publications
(105 reference statements)
0
6
0
Order By: Relevance
“…Similarly, nanoporous multilayer GO membranes fabricated by Kim et al 90 using slot-die coating and confined thermal treatment methods resulted in high PMP/PWP. Among carbon-based nanocomposites, intercalating multiwalled carbon nanotubes within lanthanum( iii ) (La 3+ )-cross-linked small-flake GO nanosheets, thereby introducing low resistance transport pathways, was found to improve PMP/PWP in the work of Nie et al 91 COF membranes were found to exceed the viscosity upper bound when a positive charge was introduced 92 or the pore size cut-off was adjusted to around 2.7 nm through slow annealing of the organic linkers. 93 On the other hand, the effect of tuning hydrophilicity or rigidity in MXene nanochannels on methanol transport is more evident compared with water transport.…”
Section: Performance Metrics Of 2d Laminated Membranesmentioning
confidence: 99%
“…Similarly, nanoporous multilayer GO membranes fabricated by Kim et al 90 using slot-die coating and confined thermal treatment methods resulted in high PMP/PWP. Among carbon-based nanocomposites, intercalating multiwalled carbon nanotubes within lanthanum( iii ) (La 3+ )-cross-linked small-flake GO nanosheets, thereby introducing low resistance transport pathways, was found to improve PMP/PWP in the work of Nie et al 91 COF membranes were found to exceed the viscosity upper bound when a positive charge was introduced 92 or the pore size cut-off was adjusted to around 2.7 nm through slow annealing of the organic linkers. 93 On the other hand, the effect of tuning hydrophilicity or rigidity in MXene nanochannels on methanol transport is more evident compared with water transport.…”
Section: Performance Metrics Of 2d Laminated Membranesmentioning
confidence: 99%
“…Various studies have been conducted where CNMs such as GO, functionalized GO, CD, CNTs, functionalized CNTs, as well as ACNPs have been used for increasing the durability and stability of the designed membranes. 166,167 These nanomaterials are proven to be mechanically, thermally, as well as chemically very stable. 168 However, the leaching of impregnated nanoparticles from the membrane media can also result in a loss of membrane performance.…”
Section: Stability and Recyclability Of Membranesmentioning
confidence: 99%
“…However, the NPs leaching out from the cast solution to the nonsolvent bath or their aggregation in the polymer bulk, during the NIPS process, prevent realizing the full potential of NPs in the membranes. , Furthermore, NP leakage to the coagulation bath or during filtration causes serious secondary pollution to our environment. Therefore, controlling NP migration and arrangement to maximize interfacial segregation is of critical importance in the fabrication of UF and MF membranes with desirable long-term performance. The importance of achieving uniform arrangement of NPs at membranes surfaces has led to many experimental investigations concerning the parameters affecting the NP migration during the NIPS process. ,, The results indicate that the surface chemistry, size, shape, and volume fraction of NPs, which determine their affinity to the host polymer, solvent, and nonsolvent, are the most influencing parameters that govern the desired migration of the NPs toward the internal (pore) and external (top) surfaces of the membranes …”
Section: Introductionmentioning
confidence: 99%